Dynamic Changes in Long-Term Exposure to Ambient Particulate Matter and Incidence of Hypertension in Adults: A Natural Experiment. Issue 3 (September 2019) - Bo, Yacong; Guo, Cui; Lin, Changqing; Chang, Ly-yun; Chan, Ta-Chien; Huang, Bo; Lee, Kam-Pui; Tam, Tony; Lau, Alexis K.H.; Lao, Xiang Qian; Yeoh, Eng-Kiong
Abstract : Many countries dedicated in mitigation of air pollution in the past several decades. However, little is known about how air quality improvement affects health. Therefore, we conducted current study to investigate dynamic changes in long-term exposure to ambient particulate matter (PM2.5 ) and incidence of hypertension in a large longitudinal cohort. We recruited 134 978 adults aged 18 years or above between 2001 and 2014. All the participants received a series of standard medical examinations, including measurements of blood pressure. The PM2.5 concentration was estimated using a satellite-based spatiotemporal model at a high resolution (1×1 km 2 ). The change in long-term exposure to PM2.5 (ΔPM2.5 ) was defined as the difference between the values measured during follow-up and during the immediately preceding visit, and a negative value indicated an improvement in PM2.5 air quality. Time-varying Cox model was used to examine the associations between ΔPM2.5 and the development of hypertension. The results show that PM2.5 concentrations increased in 2002, 2003, and 2004, but began to decrease in 2005. Every 5 µg/m 3 change in exposure to PM2.5 (ie, a ΔPM2.5 of 5 µg/m 3 ) was associated with a 16% change in the incidence of hypertension (hazard ratio, 0.84; 95% CI, 0.82–0.86). Both stratified and sensitivity analyses generally yielded similar results. We found that an improvement in PM2.5 exposure is associated with a decreased incidence of hypertension. Our findings demonstrate that air pollution mitigation is an effective strategy to reduce the risk of cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.